The Effect of Boiling Time and the Type of Utensil Used on the Nitrite and Nitrate Contents in Carrots (Daucus carota L.) - Silalahi, Jansen; Aritonang, Shena Keshia; Muchlisyam (Indonesian Journal of Pharmaceutical and Clinical Research, 2018)
Abstract. The purpose of this study was to investigate the effect of boiling time using utensils made of different metal component on thenitrate and nitrite contentsin carrots. The carrots were obtained from Jaranguda Village, Karo Regency, North Sumatra. The utensil types used for boiling were made of stainless steel, what so called periuk and aluminum and boiling time were 5 minutes, 10 minutes and 15 minutes.The determination of nitrite was done by visible spectrophotometer using sulfanilic acid and N-(1-naphthyl) ethylenediamine dihydrochloride reagentsand absorbance was measured at a wavelength of 540 nm. The determinationof nitrate wascarried out by reducing the nitrate into nitrite using Zinc powder and diluted HCl then measured as nitrite. The nitritelevel was then convertedinto nitrate. The result showed that the utensil types and boiling time affected the levels of nitrate and nitrite in carrots. The nitrate and nitrite levels in fresh carrots was 32.14 mg/kg and 24.78 mg/kg respectively. After boiling for 5 minutes, the nitrate and nitrite levels decreased significantly. Further boiling of boiled carrots, the nitrite levelincreased in the aluminum utensil from 11.00 mg/kg to 20.15 mg/kg (83 %); in periuk from 9.18 mg/kg to 16.95 mg/kg (78%) andin stainless steelfrom 8.21 mg/kg to 11.75 mg/kg (43%). While the nitrate level decreased in aluminumutensil from 27.14 mg/kg to 21.08 mg/kg (22%); stainless steel from 16.40 mg/kg to 13.25 mg/kg (19%) and periuk from 20.30 mg/kg to 16.51 mg/kg (18%). The results of this study indicated that the nitrite level increased, while nitrate level decreased with boiling time.The effect of utensil type used on boiling increased nitrite but decreased nitrate level in carrotsand these effects were found that the mostinfluential treatmentwas using utensil made of aluminum. Keyword: Carrot, Boiling Time, Nitrate, Nitrit, Utensil Type